Space covered, Type and Forms of Agricultural Information in ’Lokmat’ - Gajanan Shankar Narkar (Journal of Agricultural Extension Management, 2025)
Print media has an important role in disseminating agricultural knowledge to farmers. This paper focuses on the coverage of agricultural information in a leading Newspaper from Western Maharashtra. The objectives are to study the space covered by agricultural information and identify the different types and forms of presentation of agricultural information in the Marathi daily. It was observed that agricultural information occupied a mere (3.22%) space in the newspaper while 110n agricultural information occupied more space (68.66%). The role of print media in disseminating useful and scientific knowledge to farmers would continue to grow in future with the increasing literacy level in rural India and hence agricultural information needs to be given more coverage.